2020
DOI: 10.1001/jamaoncol.2019.4477
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Effects of Repeat Hepatectomy vs Percutaneous Radiofrequency Ablation Among Patients With Recurrent Hepatocellular Carcinoma

Abstract: IMPORTANCE Repeat hepatectomy and percutaneous radiofrequency ablation (PRFA) are most commonly used to treat early-stage recurrent hepatocellular carcinoma (RHCC) after initial resection, but previous studies comparing the effectiveness of the 2 treatments have reported conflicting results.OBJECTIVE To compare the long-term survival outcomes after repeat hepatectomy with those after PRFA among patients with early-stage RHCC. DESIGN, SETTING, AND PARTICIPANTSThis open-label randomized clinical trial was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 50 publications
4
158
1
4
Order By: Relevance
“…However, PBT and RFA yielded OS rates that were similar to those observed for RFA in randomized trials comparing the efficacy of RFA and surgical resection in early HCC. [31][32][33][34] Although the noninferiority of PBT compared to RFA was not shown in terms of the 2-year PFS as well as 3and 4-year OS in the PP analysis (Figure 2), the HRs in the PFS and OS between RFA and PBT were consistently not significant in both the ITT and PP analyses (p > 0.05 each) ( Figures 3E-H). In the best tumor response evaluation, PBT, unlike RFA, have a lagging in local control, so the median time to the best tumor response was 4.4 m (range, 1-13).…”
Section: Discussionmentioning
confidence: 92%
“…However, PBT and RFA yielded OS rates that were similar to those observed for RFA in randomized trials comparing the efficacy of RFA and surgical resection in early HCC. [31][32][33][34] Although the noninferiority of PBT compared to RFA was not shown in terms of the 2-year PFS as well as 3and 4-year OS in the PP analysis (Figure 2), the HRs in the PFS and OS between RFA and PBT were consistently not significant in both the ITT and PP analyses (p > 0.05 each) ( Figures 3E-H). In the best tumor response evaluation, PBT, unlike RFA, have a lagging in local control, so the median time to the best tumor response was 4.4 m (range, 1-13).…”
Section: Discussionmentioning
confidence: 92%
“…First, in previous studies, the number of included studies was small, and non-RCTs were included in the evaluation. Second, though several studies reported generally comparable outcomes between RHR and RFA, a tendency toward longer OS and PFS was observed in the RHR group compared with the RFA group [22,27,29]. Third, two recent high-quality studies revealed that RHR was still the most effective treatment, followed by RFA for RHCC [17,18], and the results may play an important role in the meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
“…All of the studies reported 1-, 3-and 5-year OS rates [15-18, 20-22, 26, 27, 29], while only 6 studies [16, 20-22, 26, 27] reported 1-, 3-and 5-year PFS rates. Major complications were reported in 7 studies [15,16,18,20,22,26,27]. The characteristics of the eligible studies are shown in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations